Taxes and market hours: The role of gender and skill - Robert Duval-Hernández; Lei Fang; Rachel Ngai (Federal Reserve Bank of Atlanta, 2017)
Cross-country differences of market hours in 17 countries belonging to the Organisation for Economic Co-operation and Development are mainly due to the hours of women, especially low-skilled women. This paper develops a model to account for the gender-skill differences in market hours across countries. The model explains a substantial fraction of the differences in hours by taxes, which reduce market hours in favor of leisure and home production, and by subsidized care, which frees (mostly) women from home care in favor of their market hours. Low-skilled women are more responsive to policy because of their low market returns and their comparative advantage in home activities.
Keywords: E24; E62; J22; 330; Cross-country differences in market hours; home production; subsidies on family care; Weibliche Arbeitskräfte; Arbeitszeit; Qualifikation; Hausarbeit; Lohnsteuer; Familienleistungsausgleich; Ungelernte Arbeitskräfte; Vergleich; OECD-Staaten